Different patterns of movement-related cortical oscillations in patients with myoclonus and in patients with spinocerebellar ataxia. Issue 5 (May 2019) - Visani, E.; Mariotti, C.; Nanetti, L.; Mongelli, A.; Castaldo, A.; Panzica, F.; Franceschetti, S.; Canafoglia, L.
Highlights: EEG oscillations related to Go/No-go tasks are distinctive in patients with myoclonus or ataxia. Patients with myoclonus show abnormal desynchronization/synchronization due to defective inhibition. Patients with ataxia show a defect in the lateralization of the desynchronization. Abstract: Objective: To assess whether different patterns of EEG rhythms during a Go/No-go motor task characterize patients with cortical myoclonus (EPM1) or with spinocerebellar ataxia (SCA). Methods: We analyzed event-related desynchronization (ERD) and synchronization (ERS) in the alpha and beta-bands during visually cued Go/No-go task in 22 patients (11 with EPM1, 11 with SCA) and 11 controls. Results: In the Go condition, the only significant difference was a reduced contralateral beta-ERS in the EPM1 patients compared with controls; in the No-go condition, the EPM1 patients showed prolonged alpha-ERD in comparison with both controls and SCA patients, and reduced or delayed alpha- and beta-ERS in comparison with controls. In both conditions, the SCA patients, unlike EPM1 patients and controls, showed minimal or absent lateralization of alpha- and beta-ERD. Conclusions: EPM1 patients showed abnormal ERD/ERS dynamics, whereas SCA patients mainly showed defective ERD lateralization. Significance: A different behavior of ERS/ERD distinguished the two patient groups: the pattern observed in EPM1 suggests a prominent defect of inhibition occurring in motor cortex contralateral to activated segment, whereas the pattern observed in SCA suggested a defective lateralization attributable to the damage of cerebello-cortical network, which is instead marginal in patients with cortical myoclonus.